Periconceptional Folic Acid Supplementation and Newborn Birth Weights - Lin, Jing; Wang, Cheng; Li, Sisi; Zhang, Jie; Jin, Lei; Tong, Mingkun; Meng, Wenying; Ren, Aiguo; Chen, Lei; Jin, Lei (Frontiers in Pediatrics, 2022)
Background The relationship between maternal folic acid supplementation and the birth weights of offspring remains inconclusive. Aim To examine the associations between maternal supplementation with folic acid only (FAO) or multiple micronutrients containing folic acid (MMFA) and newborn birth weights, as well as the risk of small for gestational week age (SGA) and large for gestational week age (LGA) newborns. Methods Data on 31,107 births from 2015 to 2018 were extracted from the population-based prenatal health care system in a district of Beijing. Generalized linear and logistic regression models were used to evaluate the association between maternal periconceptional folic acid supplementation and birth weights or with risk of small for gestational week age (SGA) and large for gestational week age (LGA). Results Compared with newborns whose mothers did not use any folic acid supplements, the newborns with maternal periconceptional folic acid supplementation had similar median birth weight but had a lower risk of SGA [adjusted odds ratio (aOR) = 0.81 (95% CI: 0.68–0.97)], however newborns born to mothers who took multiple micronutrients with folic acid (MMFA) with high compliance had a 25.59 g (95% CI: 6.49–44.69) higher median birth weight. Periconceptional women took folic acid only (FAO) (aOR = 0.83; 95%CI: 0.67–1.01) or MMFA (aOR = 0.74; 95%CI: 0.60–0.91) with high compliance decreased the risk of SGA, but has no impact on the risk of LGA. Conclusion Periconceptional FAO supplementation has no impact on the median birth weight of offspring and the risk of LGA. Compared with FAO, MMFA supplementation may increase the average birth weight, and a high compliance of supplementation with FAO or MMFA may reduce the risk of SGA, with MMFA having ad stronger effect than FAO.